Light-Emitting Electrochemical Cells Based on Hybrid Lead Halide Perovskite Nanoparticles - Aygueler, Meltem F.; Weber, Michael; Puscher, Bianka; Medina, Dana D.; Docampo, Pablo; Costa, Ruben Dario (Journal of Physical Chemistry C, 2015)
Methylammonium lead bromide (MAPbBr3) perovskite nanoparticles (NPs) have been recently proposed as a new material for light-emitting diodes, as well as a new paradigm to elucidate the operational mechanism in perovskite solar cells. Here, we have expanded the synthesis concept to fabricate NPs based on formamidinium lead bromide (FAPbBr3). Importantly, we have demonstrated that the photophysical features of this novel material can be easily tuned by exchanging the organic cation, achieving lower radiative bimolecular recombination rate for FAPbBr3 NPs. Additionally, we report for the first time light-emitting electrochemical cells (LECs) based on perovskite NPs by an easily up-scalable spray-coating technique. Stable luminance of 1–2 cd/m2 at low driving currents was achieved for both types of materials. Overall, this work opens a new avenue of research into the field of organic–inorganic metal halide nanoparticles bearing different alkyl ammonium groups and their application in the developing field of thin-film lighting devices.
EAM Import::2019-03-12